Effect of acute kidney injury on long‐term outcomes of spontaneous bacterial peritonitis in cirrhotic patients using the International Club of Ascites‐acute kidney injury criteria. Issue 5 (9th December 2019) - Sohn, Won; Kim, Jung Hee; Cho, Ju‐Yeon
Abstract: Background and Aim: This study aimed to investigate the effect of acute kidney injury (AKI) on long‐term mortality of spontaneous bacterial peritonitis (SBP) in cirrhotic patients using International Club of Ascites (ICA)‐AKI criteria. Methods: A total of 157 cirrhotic patients with a first episode of SBP between 2007 and 2016 were analyzed. We investigated the long‐term mortality with related risk factors of SBP in cirrhosis including the ICA‐AKI criteria. The ICA‐AKI stage at SBP diagnosis is evaluated by stages 0–3. Stage progression was defined as a progression of AKI to a higher stage. Results: The ICA‐AKI stage at the diagnosis of SBP was stage 0 in 91 (58%), stage 1 in 33 (21%), stage 2 in 19 (12%), and stage 3 in 14 patients (9%). Stage progression within 48 h after SBP diagnosis was noted in 18 patients (12%). Multivariable analysis showed that the risk factors for overall survival were age ≥ 60 years (hazard ratio [HR] 1.74, P  = 0.029), serum sodium ≤ 130 mmol/L (HR 1.3, P  = 0.017), ICA‐AKI stage 1 (HR 2.51, P  = 0.003), ICA‐AKI stage 2 or 3 (HR 3.36, P  < 0.001), and stage progression at 48 h after SBP diagnosis (HR 2.57, P  = 0.004). The differences in overall survival using the ICA‐AKI in patients without AKI using the conventional criteria were significantly different ( P  = 0.019). Conclusion: Acute kidney injury and its progression are significant risk factors for mortality in cirrhotic patients with SBP. The application of the ICA‐AKI criteria is important and advantageous for early evaluation and intervention for a better prognosis in cirrhotic patients with SBP.